A Study of Joseigo: Gendered Language of Japanese Women Workers in Ubud - Kadek Eva Krishna Adnyani; I Wayan Adnyana; Ni Nyoman Murniasih (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This study examines joseigo (japanese women’s language) differences usage found in the conversations of two Japanese women who workes in a formal and informal sector in Ubud varies in ages. The research was conducted between July and August 2016. The corpus of this study was from the conversation transcripts, interview results, questionnaire results, and observation. This study examined difference strategies used in joseigo’s linguistic features such as personal pronouns, adverbs, interjections, sentence-final forms, honorifics, and imperative sentences. The results showed that the level of formality is inversely proportional to the frequency of use of joseigo and the amount of variation used. The verbal data were majorly occurs in the formal background, joseigo forms are used less and less varied compared with the speech data that mostly occur in the informal background. On a formal background, neutral language variants (without gender attributes) are more frequently used.